Pachydermoperiostosis Accompanied by Heart Failure - Shin, Kwen-Chul (Korean Society of Echocardiography, 2009)
Pachydermoperiostosis or primary hypertrophic osteoarthropathy is an uncommon disease of acromegaloid facial feature, but characterized by unique phenotype (digital clubbing and pachydermia) and distinctive radiographic appearances like periostosis. We experienced a case with complete form of pachydermoperiostosis accompanied by heart failure. He presented with typical features consisting of clubbing with enlargement of the hand, thickening of facial skin and periosteal new bone formation involving lower leg. Echocardiography revealed severely decreased left ventricular systolic function. Treatment with medications resulted in an improvement of cardiac function and symptom. There is no previous report documenting pachydermoperiostosis accompanied by heart failure. We report that case for the first time.